Foundations of social inequality. - Feinman, Gary M.; Price, T. Douglas (Fundamental Issues in Archaeology., 1995)
"In this authoritative volume, leading researchers offer diverse theoretical perspectives and a wide-range of information on the beginnings and nature of social inequality in past human societies. Their illuminating work investigates the role of status differentiation in traditional archaeological debates and major societal transitions. This volume features numerous case studies from the Old and New World spanning foraging societies to agricultural groups and complex states. Diachronic in view and archaeological in focus, this book will be of significant interest to archaeologists, anthropologists, and students." -- Présentation de l'éditeur.